2017
DOI: 10.3164/jcbn.16-109
|View full text |Cite
|
Sign up to set email alerts
|

CAPE increases the expression of SOD3 through epigenetics in human retinal endothelial cells

Abstract: Extracellular-superoxide dismutase (EC-SOD or SOD3), which catalyzes the dismutation of superoxide anions into hydrogen peroxide, plays a key role in vascular protection against reactive oxygen species (ROS). The excess generation of ROS is closely involved in the pathogenesis of diabetic retinopathy (DR); therefore, the maintenance of SOD3 expression at high levels is important for the prevention of DR. In the present study, we showed that caffeic acid phenethyl ester (CAPE) increased the expression of SOD3 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
0
6
0
1
Order By: Relevance
“…SOD3 is known as a predominant form of SODs in plasma [ 10 ]. In many studies, it has been shown that SOD3 is mainly expressed in endothelial cells [ 11 , 26 , 27 ], and its decrease was associated with vascular endothelium damage and the infiltration of inflammatory cells [ 5 , 10 , 28 ]. In our previous study [ 29 ], we demonstrated an increased concentration of endothelium damage markers in AP patients which could be associated with decreased SOD3 concentration in the plasma of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…SOD3 is known as a predominant form of SODs in plasma [ 10 ]. In many studies, it has been shown that SOD3 is mainly expressed in endothelial cells [ 11 , 26 , 27 ], and its decrease was associated with vascular endothelium damage and the infiltration of inflammatory cells [ 5 , 10 , 28 ]. In our previous study [ 29 ], we demonstrated an increased concentration of endothelium damage markers in AP patients which could be associated with decreased SOD3 concentration in the plasma of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Exendin-4, a glucagon-like peptide-1 receptor agonist, significantly induces the expression of SOD3 in human retinal microvascular ECs (HRECs) by decreasing HDAC activity and enhancing the status of histone H3 acetylation at the SOD3 proximal promoter and ( Yasuda et al, 2016 ). Moreover, Caffeic acid phenethyl ester (CAPE) increases the transcription of SOD3 through HDAC1-regulated histone acetylation in HRECs ( Ohashi et al, 2017 ). Except for SOD3, SOD2 (Superoxide Dismutase 2, also called MnSOD) is also regulated by histone acetylation.…”
Section: Role Of Endothelial Histone Acetylation In Multiple Physiological Processesmentioning
confidence: 99%
“…Caffeic acid was also reported to attenuate high glucose concentration‐induced redox changes in other cellular types including human retinal endothelial cells and human umbilical vein endothelial cells through regulation of SOD and Nrf2. [ 46,47 ] The antioxidant capacity of A. borbonica polyphenols and caffeic acid may also result from their ability to directly scavenge ROS, as we previously showed using in vitro free radical‐scavenging assays. [ 21,22 ] Moreover, polyphenols such as caffeic acid are able to improve mitochondrial metabolism during oxidative stress.…”
Section: Discussionmentioning
confidence: 99%